EVALUATION OF INSULIN-LIKE GROWTH FACTOR-1 AND INSULINLIKE GROWTH FACTOR BINDING PROTEIN-3 IN DIAGNOSIS OF GROWTH HORMONE DEFICIENCY IN SHORT-STATURE CHILDREN - Ali, Asif; Hashim, Rizwan; Khan, Farooq Ahmad; Sattar, Abdus; Ijaz, Aamir; Manzoor, Syed Mohsin; Younas, Muhammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Growth Hormone Deficiency (GHD) is conventionally diagnosed and confirmed by diminished peak Growth Hormone (GH) levels to provocative testing. Serum Insulin-like growth factor-1 (IGF-1) and insulin-like growth factor binding protein-3 (IGFBP-3) are under the influence of GH and reflect the spontaneous endogenous GH secretion. Owing to the absence of a circadian rhythm, it is possible to take individual measurements of IGF-1 and IGFBP-3 at any time of the day for evaluation of GH status instead of subjecting the individual to cumbersome provocative tests. Objectives of this study were to compare IGF-1 and IGFBP-3 assays with Exercise and L-Dopa stimulation tests in the diagnosis of growth hormone deficiency in short stature children using ITT as gold standard. Methods: This validation study was conducted at Department of Chemical Pathology and Endocrinology, AFIP, Rawalpindi, from November 2005 to October 2006. Fifty-two short stature children were included in the study. Basal samples for GH levels and simultaneous IGF-1 and IGFBP-3 measurements were obtained and afterwards all children were subjected to sequential exercise and LDopa stimulation tests. Insulin Tolerance Test (ITT) was performed one week later with all the necessary precautionary measures. On the basis of ITT results, children were divided into two groups, i.e., 31 growth hormone deficient and 21 Normal Variant Short Stature (NVSS). Results: The diagnostic value of exercise stimulation test remained highest with sensitivity 90.3%, specificity 76.0%, Positive Predictive Value (PPV) 84.84%, Negative Predictive Value (NPV) 84.2% and accuracy 84.6%. The conventional L-Dopa stimulation had sensitivity 96.7%, specificity 38.0%, PPV 69.7%, NPV 88.8 % and accuracy 73.0%. The serum IGF-1 and IGFBP-3 levels were positively correlated with post ITT peak GH levels (r= 0.527, r=0.464 respectively, both p<0.001). The diagnostic value of IGF-1 had sensitivity 83.87%, specificity 76.2%, PPV 83.87%, NPV 76.2% and accuracy 80.76%. The diagnostic value of IGFBP-3 had sensitivity 54.83%, specificity 90.47%, PPV 89.47%, NPV 57.57% and accuracy 69.23%. With combined use of IGF-1 and IGFBP-3 diagnostic value had sensitivity 69.35%, specificity 83.33% PPV 86%, NPV 64.81% and accuracy 75%. Conclusion Growth Hormones provocative tests still remain the most useful investigations for the diagnosis of GHD. Measurements of IGF-1 and IGFBP-3 have shown comparable diagnostic performance with growth hormone stimulation tests and are valuable for patients' convenience and ease of performance and can be useful in the initial workup of short stature. Keywords: Growth Hormone Deficiency, Insulin-like Growth Factor-1, IGF-1, Insulin-like Growth Factor Binding Protein-3, Normal Variant Short Stature